Efektivitas Mikoriza Vesikular Arbuskular dan 5-aminolevulinic Acid terhadap Pertumbuhan Jagung Varietas Lokal Madura pada Cekaman Kekeringan - Hamida, Ruly; Dewi, Kumala (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2015)
The local Madura maize variety planted on drought stress area suffered retarded plant growth and reduced grain yield. Research was conducted to alleviate the stress on crop plants, to survive under drought condition. The aim of this study was to investigate the effects of MVA and ALA on the growth of Guluk-guluk local maize variety planted under difference drought stresess. The experiment was conducted using split-split plot design with three factors in six replications. The first factor was variation of MVA application, i.e., without inoculation (M0) and with inoculation of mycorrhiza (M1). The second factor was ALA treatment which consisted of 3 levels, namely 0% (P0), 0.05% (P1) and 0.1% (P2). Third factor was plant watering intensity, i.e., watered once every 2 days (K0), watered once every 4 days (K1) and watered once every 6 days (K2) reaching field capacity, respectively. Data were analyzed by two-way ANOVA and Duncanâs Multiple Range Test (DMRT). The results suggested that MVA and ALA treatments gave significant effects in increasing the percentage of mycorrhiza infection, total leaf P content, total chlorophyll content, plant height, fresh and dry weight of shoot and root and shoot/root ratio. It showed a significant effect in decreasing ABA content in maize plant subjected to drought stress. The ABA content was 1.7 ppm in plants watered once every 2 days, where control plant had ABA content of 5.8 ppm. The best treatment was found on plants treated with mycorrhiza inoculation and 0.05% ALA and watered once every 4 days.